2001
DOI: 10.1073/pnas.171105098
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of spinal muscular atrophy by sodium butyrate

Abstract: Spinal muscular atrophy (SMA) is an autosomal recessive disease characterized by degeneration of the anterior horn cells of the spinal cord, leading to muscular paralysis with muscular atrophy. No effective treatment of this disorder is presently available. Studies of the correlation between disease severity and the amount of survival motor neuron (SMN) protein have shown an inverse relationship. We report that sodium butyrate effectively increases the amount of exon 7-containing SMN protein in SMA lymphoid ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
271
1
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(281 citation statements)
references
References 35 publications
(40 reference statements)
6
271
1
3
Order By: Relevance
“…Recent in vivo studies have shown that treatment with HDAC inhibitors of a wide range of structures provide neuroprotective effects in models of various motor neuron disorders. [44][45][46][47] However, the roles of glia under therapeutic mechanisms of HDAC inhibitors were not investigated. Here we showed that the neurotrophic effects of VPA, a HDAC inhibitor of short-chain fatty acid structure, were associated with Figure 5 VPA is neuroprotective against LPS-induced DA neurodegeneration in rat primary mesencephalic neuronglia cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent in vivo studies have shown that treatment with HDAC inhibitors of a wide range of structures provide neuroprotective effects in models of various motor neuron disorders. [44][45][46][47] However, the roles of glia under therapeutic mechanisms of HDAC inhibitors were not investigated. Here we showed that the neurotrophic effects of VPA, a HDAC inhibitor of short-chain fatty acid structure, were associated with Figure 5 VPA is neuroprotective against LPS-induced DA neurodegeneration in rat primary mesencephalic neuronglia cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of HDAC activity was reported to be associated with neuroprotective effects in experimental models of motor neuron disorders by HDAC inhibitors with different chemical structures. [44][45][46][47] Preliminary results from our laboratory suggests that inhibition of HDAC in astroglial cultures is related to the increase in the expression of GDNF and BDNF by VPA treatment (Wu et al, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 As the differences between SMN1 and SMN2 are related to the complete transcript and the amount of protein, drugs capable of increasing FL-SMN expression and SMN protein may have therapeutic effects for SMA patients. 13 Histone deacetylases inhibitors (HDACi), for example, increase acetylation of histones and other proteins 14 and this hyperacetylation relaxes the tertiary structure of chromatin, facilitating access of the transcriptional machinery to target genes. In vitro experiments with phenylbutyrate (PBA) and valproic acid (VPA) -two well-known HDACi -have shown an increase in SMN mRNA and protein levels in SMA fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Some genes may simply require histone hyperacetylation to be turned on or to upregulate their transcriptional output. This the case of the ALDPL1 [Kemp et al, 1998] and SMN2 genes [Chang et al, 2001;Andreassi et al, 2004], involved in adrenoleukodystrophy and spinal muscular atrophy, respectively. Transcriptional activation could partially compensate for disease causing mutations in these two genes.…”
Section: Transcriptional Therapy Of Fragile X and Other "Epigenetic" mentioning
confidence: 98%